Recreating the shading effects of ship wake induced turbidity to test acclimation responses in the seagrass Thalassia hemprichii - Browne, Nicola; Yaakub, S.; Tay, J.; Todd, P. (Academic Press, 2017)
Elevated sediment delivery and resuspension in coastal waters from human activities such as shipping can have detrimental effects on seagrass health by limiting light penetration. Managing seagrasses requires knowledge of their light acclamatory abilities so guidelines for coastal activities (e.g. ship movements) that influence sediment dynamics can be created. Guidelines typically focus on ensuring that seagrasses are able to meet their minimal light requirements (MLR). MLRs can be achieved by different light regimes, but it remains unknown whether a chronically low yet stable light regime is less or more detrimental than a highly variable regime with periods of extreme low to no light. To test this, we compared the physiological and morphological responses of Thalassia hemprichii among three light regimes: an open control (30-40% ambient light), a shaded control with (11-15% ambient light), and a fluctuating shade (4-30% ambient light). The MLR for the T. hemprichii we studied was lower (4-10% ambient light) than previous reports (mean = 18%) illustrating enhanced light acclimation in Singapore's chronically turbid waters. Seagrass shoots in the shaded control, however, exhibited significantly more morphological stress symptoms, with reduced shoot growth and lower below ground biomass. These data suggest that for seagrass exposed to periods of acute light stress, energetic costs associated with photo-acclimation to more variable light regimes can be offset if the plant can meet its daily light requirements during periods of high light. Management of seagrass beds should incorporate regular light monitoring and move towards an adaptive feedback-based approach to ensure the long-term viability of these vulnerable ecosystems.